The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.2174/1872211308666140926112000
|View full text |Cite
|
Sign up to set email alerts
|

Recent Patents on Ophthalmic Nanoformulations and Therapeutic Implications

Abstract: Nanoformulations (NF) are widely explored as potential alternatives for traditional ophthalmic formulation approaches. The effective treatment of ocular diseases using conventional eye drops is often hampered by factors such as: physiological barriers, rapid elimination, protein binding, and enzymatic drug degradation. Combined, these factors are known to contribute to reduced ocular residence time and poor bioavailability. Recent research studies demonstrated that NF can significantly enhance the therapeutic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 27 publications
0
25
0
1
Order By: Relevance
“…can inhibit the activity of P-gp expressed on epithelial cells [60], and open corneal tight junctions by means of non-ionic surfactants present in the formulations [12]. In the treatment of posterior segment diseases, they can act as controlled release systems that reduce administration frequency.…”
Section: Colloidal Carriers For Ocular Deliverymentioning
confidence: 99%
See 2 more Smart Citations
“…can inhibit the activity of P-gp expressed on epithelial cells [60], and open corneal tight junctions by means of non-ionic surfactants present in the formulations [12]. In the treatment of posterior segment diseases, they can act as controlled release systems that reduce administration frequency.…”
Section: Colloidal Carriers For Ocular Deliverymentioning
confidence: 99%
“…However, in some cases this produces a sticky feel of the formulation and subsequent intolerance [60].…”
Section: Colloidal Carriers For Ocular Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…By de inition, nano emulsions have dispersed phase in which the particle size is in the submicron or nanometer range. Nano-emulsions generally comprise of one or more amphiphilic lipid(s) or surfactants [1].To increase the bioavailability of a drug in terms of ocular disease, the time that the drug stays on the cornea must be increased. There must be a set viscosity on the ocular formulations and a way to improve the viscosity is by increasing the amount of the oil face that is present in the nano-emulsion, thereby increasing the time that the drug settles on the cornea.…”
Section: Nano-emulsionmentioning
confidence: 99%
“…Recent research studies demonstrated that nanoformulations can signi icantly enhance the therapeutic ef icacy and bioavailability of ocular drugs, compared to the established classical ophthalmic drug delivery strategies [1]. There are over seventy different conditions relating to the eye that have been characterized as an ophthalmological disease.…”
Section: Introductionmentioning
confidence: 99%